Perceived Socio-economic, Socio-ecological and Socio-cultural Impacts of the Caribbean’s Tourism Sector - Christian, Colmore; Herbert, Berneece (Advances in Social Sciences Research Journal, 2016)
A self-administered questionnaire was administered to participants attending the Caribbean Tourism Organization’s 2010 Sustainable Tourism Conference held on Barbados to assess their motivation to attend the conference, their satisfaction with the contribution and impact of region’s tourism sector, and the level of involvement of the youth in sector. The results of the analysis point to a strong interest in the annual Sustainable Tourism Conferences. Over 70% of participants were motivated to attend for the purposes of broadening their tourism knowledge base or for networking. The overall impacts of tourism at the community, national and regional levels seem to be acceptable to participants, but close to 15% of respondents expressed dissatisfaction. There was concern however about the level of involvement of the youth and the extent to which they benefited from the rewards of the tourism sector. This environment of concern may be an opportune time for the Caribbean Tourism Organization (CTO) to consider mechanisms and strategies to attract and engage more youth to the sector. Indeed, there is a need for enhanced cooperation and coordination among CTO member governments, regional and international organizations, the private sector, and civil society actors, to harness the potential of youth for the benefit of the tourism sector. In this regard a few specific initiatives such as a Youth Tourism Ambassador Program and a Youth Tourism Mentors Program have been proposed. The need for more directed and deliberate investments in training programs targeted at the youth should also be considered. The practical implications of the study are discussed, as well as its limitations and scope for future research.